General paediatrics outpatient consultation fees, bulk billing rates and service use patterns in Australia - Gary L. Freed; Amy R. Allen (Elsevier, 2018)
Abstract Objective: To determine: 1) the mean, median and range of fees for initial and subsequent private outpatient consultations with a general paediatrician in Australia; 2) any variation in fees and bulk billing rates between states/territories; and 3) volume of outpatient general paediatric specialist consultations relative to child population. Methods: Analysis of Medicare claims data from the years 2011 and 2014 for initial consultations (items 110 and 132), subsequent consultations (items 116 and 133), and autism or pervasive developmental disorder (PDD) initial consultation (item 135) with a general paediatrician. Results: Fees for initial and subsequent general paediatric outpatient consultations varied within, and between, states and territories. Fees increased slightly from 2011 to 2014, after accounting for inflation. The volume of consultations relative to child population varied markedly across states and territories, as did bulk billing rates. Use of item codes for patients with multiple morbidities (132 and 133) increased significantly from 2011 to 2014. Autism/PDD consultation service use (item 135) and fees remained relatively stable. Conclusions: There was variation in service use, fees and bulk billing within, and between, states and territories, and across time and consultation types. Implications for public health: Future studies should assess the impact of such variation on access to paediatric services and the relationship, if any, to variation in state investment in public paediatric outpatient services.